DETERMINANTS OF PROACTIVE CAREER BEHAVIOUR AMONG FEMALE WORKERS: PROACTIVE PERSONALITY AS A MODERATOR - Sin Yee Cheong; Cheng Ling Tan; Jian Ai Yeow; Chew Sze Cheah (International Journal of Accounting, Finance and Business, 2020)
Nowadays, the increasing trend of female labour force participation in Malaysiasignifies a positive impact on Malaysia gross domestic product (GDP) which helps to boost theeconomy. Many companies begin to realise the significance of women in the organization asthey will help to improve the quality of engagement and mutual understanding betweenorganizations and the community. Nevertheless, the proactive career behaviour of womenbecomes more vital to be understood for encouraging and retaining women in the workplace.Female employees slowly become an important contributor to today's economy and yet, thereis scare of researches on this related topic. In this, the researchers are motivated to study thedeterminants of proactive career behaviour among female employee. This study is based on150 female employees who work in the private sectors in Peninsular Malaysia. The motivatingfactors include future work self, career adaptability, perceived career barriers, dispositionalhope and proactive personality. The moderator role of proactive personality was also assessedin the model. Descriptive and inferential statistics are used to determine the relationshipbetween those variables. In this research, the result has shown that future work self andproactive personality are significant influence the proactive career behaviour of femaleemployees. Contrary to our expectation, there is insufficient evidence to support moderatingeffects in the study. This study contributes some implication to management to act to foster theproactive behaviour of female employees. Common method variance and generalisation issuedue to small sample size are some of the limitations. Thus, some recommendation for futureresearch were laid out in the study.